汉语“经常”“常常” “往往”与印尼语“SERING”的对比分析 COMPARISON OF “JINGCHANG” “CHANGCHANG” AND “WANGWANG” IN MANDARIN WITH THE WORD “SERING” IN INDONESIAN - Sinar Anwar (Journal of Language, Literature and Teaching, 2021)
The words